2010
DOI: 10.1073/pnas.1001637107
|View full text |Cite
|
Sign up to set email alerts
|

Type III restriction enzymes cleave DNA by long-range interaction between sites in both head-to-head and tail-to-tail inverted repeat

Abstract: Cleavage of viral DNA by the bacterial Type III RestrictionModification enzymes requires the ATP-dependent long-range communication between a distant pair of DNA recognition sequences. The classical view is that Type III endonuclease activity is only activated by a pair of asymmetric sites in a specific head-to-head inverted repeat. Based on this assumption and due to the presence of helicase domains in Type III enzymes, various motor-driven DNA translocation models for communication have been suggested. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 38 publications
3
74
3
Order By: Relevance
“…6). Our method is therefore particularly recommended for applications involving high forces, limiting molecule lengths, or low frame rates, such as high-resolution tracking of molecular motors (6,24,26), mechanical sequencing of DNA (34), or highly parallelized measurements on many molecules (48)(49)(50). In general, our calibration scheme does not exhibit any disadvantages compared to calibrations based on the short-pendulum geometry.…”
Section: Discussionmentioning
confidence: 98%
“…6). Our method is therefore particularly recommended for applications involving high forces, limiting molecule lengths, or low frame rates, such as high-resolution tracking of molecular motors (6,24,26), mechanical sequencing of DNA (34), or highly parallelized measurements on many molecules (48)(49)(50). In general, our calibration scheme does not exhibit any disadvantages compared to calibrations based on the short-pendulum geometry.…”
Section: Discussionmentioning
confidence: 98%
“…Translocation without loop formation has also been suggested [18]. However, other studies did not find evidence for either long-lived DNA loops or directional translocation [12,19,20]. Alternatively, it was suggested that ATP is used to catalyse a conformational switch from DNA recognition to one-dimensional DNA diffusion (also known as ‘DNA sliding’) [8,19].…”
Section: The Atp-dependent Type III Rm Enzymesmentioning
confidence: 99%
“…The absence of apparent looping in the TPM assay when applied to the type III R/M enzymes is also cited as support for the MT model (13,14), but it is apparent that the data are not of sufficient resolution, when compared with the data obtained for the Ecl18kI type II restriction enzyme, to rule out looping (32). It is important to note that DNA looping and one-dimensional diffusion along a DNA contour are both fast events occurring on the millisecond timescale, much faster than the time resolution of the assays currently employed, be they single molecule or ensemble assays (1,38,39).…”
Section: Introductionmentioning
confidence: 99%